EVALUATION OF EFFECTIVENESS OF ERGONOMIC INTERVENTION FOR OVERHEAD WORKS AT THE CONSTRUCTION INDUSTRY - BAHTIAR EFENDI (NIM : 23408045), IMADUDDIN
To win competition, productivity is highly required, mostly on human resource productivity. Protections and prevention actions from sickness and accidents are required. The main factors are fatigue and works that may cause risk work related musculoskeletal disorders (WMSDs) to happen. An assessment of the characteristics of overhead works and its risks is highly required. An ergonomic intervention along working methods is required as one of the efforts to decrease fatigue and work risk level. Meanwhile, a selection for assessment method to make sure that costs, time, and human resources are working efficiently. The purpose of this research is to evaluate ergonomic intervention effectivity (the use of new machineries) toward the development of fatigue and work risk level in the overhead works at construction industry using 2 approach, they are direct measurement and computer simulation. There are 24 male respondents involved in this research. Direct measurement was used to know the development of fatigue measured by the change of each respondentÃ‚Â’s grip and maximum voluntary contraction (MVC) of deltoid muscle. The assessment of work risk level was done by taking pictures of each working posture/position, then simulated in biomechanics software, 3 Dimensional Static Strength Predicition Program (3DSSPP). Respondents casted putty at the ceiling for two days, two hours at each day. At day one, respondents casted putty using conventional tool; and at day two, they used a modified casting tool. The modified tool used, ERGOSC, was invented by Zulfahmi (2009). During the experimentation the development of fatigue was measured every 20 minutes for two hours; while the working postures were randomly selected toward four main overhead work-postures. The result of this research shows that there is a consistency between direct measurement and simulation; showing that the modified tool (ERGOSC) has the ability to decrease fatigue and work risk level. The result is consisten, yet direct measurement is still required to measure fatigue. It is highly recommended to further develop ERGOSC in the construction industry.